Association between the ratio of serum creatinine to cystatin C and bone mineral density in Chinese older adults patients with type 2 diabetes mellitus - Gao, Ting; Liu, Fupeng; Ban, Bo; Hou, Yue; Li, Guangxin; Jiang, Mingming; Yang, Qing; Zhang, Mei (Frontiers in Nutrition, 2022)
Background The ratio of creatinine to cystatin C (Cre/CysC), a marker of muscle function and muscle mass, can be used to predict sarcopenia in different populations. Since sarcopenia is closely associated with osteoporosis, this study investigated the association between Cre/CysC and bone mineral density (BMD) in patients with type 2 diabetes mellitus (T2DM). Method This cross-sectional study included 391 Chinese patients with T2DM. General information, biochemical indicators, and the BMD of lumbar spine (LS), femoral neck (FN), and total hip (TH) were measured. Results Pearson correlation analysis showed that Cre/CysC was significantly positively correlated with the BMD of LS (r = 0.170, p = 0.001), FN (r = 0.178, p < 0.001), and TH (r = 0.205, p < 0.001). The results of stepwise linear regression suggested that Cre/CysC was the only biochemical predictor of the BMD at three sites (LS: β = 0.137, p = 0.01; FN: β = 0.097, p = 0.038; TH: β = 0.145, p = 0.002). Conclusion In older patients with T2DM, high Cre/CysC value is independently positively associated with BMD and hence, Cre/CysC may serve as a valuable marker of osteoporosis.